KOMUNIKASI PERSUASIF LEMBAGA PENGKAJIAN PANGAN, OBAT-OBATAN DAN KOSMETIKA MAJELIS ULAMA INDONESIA (LPPOM MUI) DALAM MENINGKATKAN KESADARAN PENTINGNYA SERTIFIKAT HALAL KEPADA PENGUSAHA CATERING DI PEKANBARU - Iqlimaturrajmi "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
LPPOM MUI was established on January 6, 1989 based on the Decree of Majelis Ulama Indonesia Number: Kep./18/ MUI / I / 1989, with the main activity plan to carry out inspection of halal product which then called halal certification. This halal certification activity is intended to obtain a halal product guarantee. Catering entrepreneurs in Pekanbaru are still many who do not have halal certificate and are still concerned with the interests of the tender solely than the interests of consumer health, halal certification process is done so that people in Pekanbaru more intelligent to choose and consume foods that are clearly halal according to the teachings of Islamic Shari'ah. LPPOM MUI Riau will go down the field directly with a deep search to know exactly whether the materials used in the manufacture of a food product and its production process has been guaranteed to be halal and consistent or not.This research uses qualitative research method with descriptive approach. The subjects consisted of five catering entrepreneurs who were selected by using Purposive Sampling. Data collection is done through in-depth interviews, observation and documentation. To perform the validity of data, the authors use extension opt-in techniques, observational persistence and triangulation.The result of the research proves that the lack of awareness level from catering businessman in Pekanbaru to take care of halal certificate, because not yet out of Law RI 33 Year 2014 about the guarantee of halal product. The law itself already exists, but the derivative of the Act itself is not yet. For now this LPPOM MUI is still just fostering how Muslims can produce everything good food, toyiban stuff. If the Act is already officially signed out and executed then the catering entrepreneur must have halal certificate.